IMPLIKATUR DALAM PERCAKAPAN SELEBGRAM BALI GEK_CANTIK25 - Anak Agung Istri Manik Warmadewi (Linguistik : Jurnal Bahasa dan Sastra, 2021)
Celebgram is a phenomenon that appears in the community. Celebgrams also have an influence on their followers on Instagram accounts. The content made must be interesting, so that it can make them a celebrity. in each content, some are in the form of a monologue, some are in the form of dialogue. With regard to dialogue or conversation, it cannot be separated from pragmatic studies, one of which is the implications in speech acts. This research is a qualitative research, with the data source of Balinese celebrities who are celebrities on Instagram social media. Selebgram which is the source of the data uses Balinese in the video upload. The results of the discussion on the existing problems, found three forms or three types of speech acts which are conversational implicatures based on the theory put forward by Searle. The types of speech acts found were assertive, declarative, and expressive.Â